Metastatic renal cell carcinoma without evidence of a renal primary - Costantino, Corey (Int Urol Nephrol, 2015)
PURPOSE: Metastatic renal cell carcinoma (RCC), without an identified kidney primary, has been reported rarely. We report a patient with RCC metastatic to bilateral adrenal glands and liver, without an apparent renal primary. We detail the immunohistochemical and molecular studies employed to substantiate the diagnosis of RCC and direct therapy. METHODS: Histopathologic findings were correlated with imaging data and supplemented by a panel of immunohistochemical stains, as well as tumor sequence analysis. RESULTS: Despite the presence of bilateral adrenal masses and lack of tumor within kidney parenchyma, the diagnosis of RCC was substantiated by immunohistochemistry (RCC+/PAX2+/PAX8+/Melan-A−/SF-1− among others) and molecular genetic analysis, harboring mutations in VHL, TP53, KDM5C, and PBRM1. After debulking surgery, based on the diagnosis of RCC and the molecular profile, the patient was treated with a tyrosine kinase inhibitor (sunitinib), resulting in stablilization of disease. CONCLUSIONS: This case illustrates the role of mutational analysis in carcinomas with rare or unusual presentations, such as metastatic RCC without a renal primary.